(untitled) (The Pakistan Development Review, 1996)
Despite a gradual increase over the past twenty years, the rate of private saving in Pakistan remains low as compared with many of the developing economies in Asia. Empirical analysis of the long-run behaviour of saving in Pakistan suggests that financial deepening, though still at a relatively early stage of development, accounted for much of the rise in private saving. In contrast with the experience in the economies of Southeast Asia, where the demographic structure of the population changed significantly over the past two decades, high rates of population growth have kept the age structure of Pakistan’s population virtually unchanged and appear to account for the disparity between the saving rates in Pakistan and Southeast Asia. Hence, an increase in the long-run rate of private saving will likely require further financial development and a decline in the growth rate of the population.